Hutang Piutang Dibayar dengan Hasil Panen dalam Perspektif Hukum Islam di Gadingrejo - Arifuat Marzuki (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
This research discusses about debts practice which the return is taken from the harvest, this practice has long and often happened. This research aims to answer the questions in the formulation of the problem, namely to describe practice debts which the return is taken from the harvest in Gadingrejo village, Kepil subdistrict, Wonosobo district.Then describe the debt agreement contract to find out the chronology of the occurrence of accounts payable practices and answer how Islamic law reviews about regarding the practice of these accounts payable. This type of research is field research, the data which collected by the author includes how the practice of accounts payable is paid with the yield of the data source collected through the community of Gadingrejo Village Kepil District Wonosobo District especially the people who practice it and literature from books that support the theory so that it can be analyzed the implementation of accounts payable debt paid with yields that occur in the village Gadingrejo village Kepil subDistrict Wonosobo district is a contract that is not in accordance with the agreement agreed at the beginning of the contract agreement so that the law becomes invalid or damaged.